Formulation and Antioxidant Testing of Gold Nanoparticles Serum from Arabica Coffee Husk Extract (Coffea arabica L.) as an Anti-Aging Agent - Yetti Hariningsih; Syamsul Ma'arif; Siti Nurhayati; Jihan Khoiriyyah (MEDFARM: Jurnal Farmasi dan Kesehatan, 2026)
Arabica coffee bean husks (Coffea Arabica L.) are known to contain polyphenols, one of which is flavonoids, which have the potential to act as bioreductive agents in the biosynthesis of gold nanoparticles. Gold nanoparticles are widely used in cosmetics because they can increase skin elasticity, improve skin metabolism, and have anti-aging properties. The purpose of this study was to formulate a gold nanoparticle serum using coffee bean skin extract and determine its antioxidant effectiveness. The gold nanoparticle biosynthesis method used in this study was the green synthesis method, while the method used to test antioxidant activity was the DPPH (2,2-diphenyl-2-picrylhydrazyl) method. Characterization results of gold nanoparticles from Arabica coffee fruit peel extract showed a color change from yellow to purple. The results of the physical quality evaluation of gold nanoparticle serum from Arabica coffee fruit peel extract at F1 with a pH of 6.45 ± 0.05, viscosity 933.75 ± 13.77 cP, and spreadability 6.20 ± 0.08. F2 with pH 6.20 ± 0.08, viscosity 917.50 ± 11.90 cP, and spreadability 6.43 ± 0.05. F3 with pH 5.90 ± 0.08, viscosity 987.50 ± 6.55 cP, and spreadability 6.6 ± 0.08. The antioxidant activity results of Arabica coffee fruit peel extract nanoparticles showed an IC50 value of 9.826, Vitamin C at 1.653, both of which have very strong antioxidant activity, while the gold nanoparticle serum from Arabica coffee fruit peel at 53.239 has strong antioxidant activity because it has an IC50 value in the range of 50–100 Keywords: consist Gold nanoparticles; Arabica coffee fruit skin; Serum; Antioxidant